2016
DOI: 10.1108/dat-08-2015-0048
|View full text |Cite
|
Sign up to set email alerts
|

Gender, recovery and contemporary UK drug policy

Abstract: including the URL of the record and the reason for the withdrawal request. Gender, Recovery and Contemporary UK Drug Policy PurposeThe article provides a gendered reading of the 2010 UK drug strategy and draws out the implications of the new recovery paradigm for female drug users. DesignThe article explores the concept of recovery at a theoretical level, uncovering the taken-for-granted assumptions in the three overarching principles: freedom from dependence; well-being and citizenship. It also analyses the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 25 publications
2
29
0
Order By: Relevance
“…Narrative analysis suggests that young people's shame regarding their parents' drug use and fear that their parents may be arbitrarily killed are constructed by young people as domestic problems to be dealt with by them alone. This resonates strongly with findings from other contexts, where responsibility for drug harms is centred on individuals, rather than enabling attention to the range of factors that interact to make communities vulnerable to these harms (Wincup, 2016). Crucially, this paper contrasts starkly with that of valentine and Smyth, demonstrating the important role of policy contexts in shaping the affective experience of families impacted by drug use.…”
Section: Parents Who Use Drugs and Techniques Of Surveillancesupporting
confidence: 70%
“…Narrative analysis suggests that young people's shame regarding their parents' drug use and fear that their parents may be arbitrarily killed are constructed by young people as domestic problems to be dealt with by them alone. This resonates strongly with findings from other contexts, where responsibility for drug harms is centred on individuals, rather than enabling attention to the range of factors that interact to make communities vulnerable to these harms (Wincup, 2016). Crucially, this paper contrasts starkly with that of valentine and Smyth, demonstrating the important role of policy contexts in shaping the affective experience of families impacted by drug use.…”
Section: Parents Who Use Drugs and Techniques Of Surveillancesupporting
confidence: 70%
“…Three women indicated that drug addiction was both an offending motivation and a pathway into crime, reinforcing the already‐recognised link between drugs and offending behaviour (Surratt et al . ; Wincup ). All three women were very clear on the impact that drug‐taking had on their continued involvement in offending.…”
Section: Research Findingsmentioning
confidence: 99%
“…However, the term remains contested (e.g. Valentine, 2011; Wincup, 2016), and there is no equivalent definition for the recovery experience of the family member.…”
Section: And the Betty Fordmentioning
confidence: 99%